Waste-to-energy: Producer gas production from fuel briquette of energy crop in Thailand - Kittikorn Sasujit (2018)
Biomass is a renewable source of energy with environment-friendly carbon neutral characteristics. World-wide, a considerable amount of biomass is available in the form of wastes whose economy is primarily dependent on agricultural production. In the present work, an experimental investigation has been conducted using briquette of oil palm and tung tree wastes through downdraft gasification process. The effect of the low heating value of producer gas, gasification efficiency, producer gas yields and tar concentration by variation equivalence ratio were presented. The experimental results showed that gasification performance was the optimum value of equivalence ratio is 0.385 and 0.372. The optimum low heating value of producer gas containing 3.20 MJ/Nm3 and 3.23 MJ/Nm3, gas yield was 4.46 Nm3/kg and 3.72 Nm3/kg, gasification efficiency was 76.24% and 70.15%, furthermore, tar concentration was 89.90 g/Nm3 and 71.71 g/Nm3, respectively. Finally, briquette from oil palm and tung tree waste can be converted to producer gas production and utilized for internal combustion engine for electricity.